Genomic structure and diversity of oak populations in British parklands. Issue 2 (14th September 2021) - Nocchi, Gabriele; Brown, Nathan; Coker, Timothy L. R.; Plumb, William J.; Stocks, Jonathan J.; Denman, Sandra; Buggs, Richard J. A.
Societal Impact Statement: The largest populations of veteran oak trees in Europe are found in British parklands: managed wood pastures up to 1000 years old. Here, we present genomic evidence that parkland oak populations harbour considerable diversity and grew from local seed sources. We found some evidence for natural regeneration of offspring and for hybridization between pedunculate and sessile oak. We detected signatures of past gene flow between these two species and few regions of high differentiation within their genomes. Future expansion of this dataset may allow us to test for a genomic basis of acute oak decline, a syndrome of particular concern in parkland environments. Summary: The two predominant oak species in Europe, Quercus robur (English or pedunculate oak) and Quercus petraea (sessile oak), have a long history of human intervention. In Britain, a common management regime is parklands, often surrounding country houses. Little is known about how seeds were sourced for parkland oak populations nor the genetic diversity that they contain. We sequenced the whole genomes of 386 trees from four British parkland sites to characterize the nuclear and chloroplast genetic structure and diversity of oak parkland populations. We assembled the chloroplast genomes and matched these to restriction enzyme fragment chloroplast haplotypes found in previous studies of ancient woodlands. We found over two million high‐quality nuclear single‐nucleotide polymorphisms (SNPs), allowing us to identify 360 Q. robur, 10 Q. petraea and 16 hybrid individuals with confidence. We identified 81 coding regions exhibiting strong differentiation between the two species. We found evidence for selective sweeps in Q. robur near some regions containing genes with putative involvement in stress tolerance. We detected a few very close relatives within some sites, suggesting natural regeneration or local seed planting. There was little differentiation among the Q. robur populations at the four sites. Chloroplast genomes found in each parkland tended to be similar to those of local ancient woodlands, suggesting that they were derived from local seed sources. Abstract : The largest populations of veteran oak trees in Europe are found in British parklands: managed wood pastures up to 1000 years old. Here, we present genomic evidence that parkland oak populations harbour considerable diversity and grew from local seed sources. We found some evidence for natural regeneration of offspring and for hybridization between pedunculate and sessile oak. We detected signatures of past gene flow between these two species and few regions of high differentiation within their genomes. Future expansion of this dataset may allow us to test for a genomic basis of acute oak decline, a syndrome of particular concern in parkland environments.